MRI Human Brain Segmentation / Classification Using Bayesian Techniques - Safa, Soodabeh (2010)
This project investigates automated or semi-automated statistical techniques for segmentation or classification of MR human brain images for tissues, like Gray Matter (GM), White Matter (WM), CSF (Celebro-Spinal Fluid).